Using criminal histories to empower victim–survivors of domestic abuse. (May 2023) - Hadjimatheou, Katerina
The Domestic Violence Disclosure Scheme (DVDS) was first introduced in England and Wales in 2014 and has since been reproduced across the world. Its aim is to empower victim–survivors by giving them access to a partner's criminal history and thereby helping them make informed decisions about their relationship. Yet the relationship between information and empowerment in this context remains contested and unexplored both theoretically and empirically. This paper draws on findings from the largest qualitative study of the DVDS to date as well as coercive control, to show that police are using disclosures to undermine perpetrators' 'monopolies on perception' and in doing so aiming to empower victim–survivors to redefine their own realities. The implications for practice-oriented models of empowerment and evaluation methodologies are explored.